2018
DOI: 10.3991/ijet.v13i09.7841
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of two Gamified Emotional Education Software’s in Emotional and Well-being Variables in Spanish Children and Adolescents

Abstract: The aim of the present research is to explore the differences among emotional and well-being variables in primary and secondary education students after undergoing the software’s Happy 8-12 and the Happy 12-16 during an academic course. Both innovative software’s are focused in the training of the basic emotional competences. The study has a pre-post quasi-experimental design with a control group. A total of 574 primary education students and 903 of secondary education participated in the study. Results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
2
19
1
Order By: Relevance
“…(1) face-to-face instruction and (2) game-based e-learning instruction. The findings of this study indicate that it is possible to improve academic achievement across the two methods; however, similar to other studies (Mysirlaki and Paraskeva, 2015;Ros-Morente et al, 2018;Gray et al, 2019;Nikolaou et al, 2019), the improvement was found to be more significant when gamebased e-learning was used. In addition, teacher satisfaction with the 7-week training program was very high for both methods.…”
Section: Discussionsupporting
confidence: 85%
“…(1) face-to-face instruction and (2) game-based e-learning instruction. The findings of this study indicate that it is possible to improve academic achievement across the two methods; however, similar to other studies (Mysirlaki and Paraskeva, 2015;Ros-Morente et al, 2018;Gray et al, 2019;Nikolaou et al, 2019), the improvement was found to be more significant when gamebased e-learning was used. In addition, teacher satisfaction with the 7-week training program was very high for both methods.…”
Section: Discussionsupporting
confidence: 85%
“…This indicates that digital newspapers publish only part of the reality of the situation, because scientific literature demonstrates exactly the opposite on this issue. For instance, several studies indicate that children frequently use video game apps on smartphones and these are now a fundamental entertainment activity for teenagers [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in primary and secondary schools computer games can be used for simulating conflicts which occur in everyday life situations. By recognizing and controlling their emotions while in simulated conflicts, students acquire emotional competence [13]. Computer games can also be used for learning of safety education by pre-school children, e.g.…”
Section: Related Workmentioning
confidence: 99%